Gamma '-phase reinforced cobalt-based high-temperature alloy for LPBF process and preparation method of gamma'-phase reinforced cobalt-based high-temperature alloy

By using the γ’ phase to strengthen the cobalt-based high-temperature alloy in the LPBF process, adjust the content and distribution of Ta and Ti elements, control the precipitation morphology of the γ’ phase, and form a mesh γ’ phase, solving the high-density dislocation structure and non-weldability problems of high-temperature alloys in the LPBF process, achieving excellent mechanical properties and thermal stability.

CN119640098AActive Publication Date: 2025-03-18HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411543471.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-18
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing high-temperature alloys often have high-density dislocation structures in the LPBF process, resulting in inducing recrystallization during solid solution-aging heat treatment, losing columnar crystals and strong texture advantages, and having strong weldability and a large number of crack defects.

Method used

The cobalt-based high-temperature alloy is strengthened by adjusting the content and distribution of Ta and Ti elements, and using their characteristics of partial aggregate in high-density dislocation structures, the precipitation morphology of the γ’ phase is controlled to form a network γ’ phase, breaking the traditional block-shaped L12 morphological structure.

Benefits of technology

It is realized that high-temperature alloys with excellent room temperature and high temperature mechanical properties are obtained in the LPBF process, and solid solution heat treatment is avoided, columnar crystals and strong texture morphology are maintained, and the thermal stability of the material is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640098A_ABST
    Figure CN119640098A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal additive manufacturing, and provides a gamma'phase reinforced cobalt-based high-temperature alloy for an LPBF process and a preparation method of the gamma 'phase reinforced cobalt-based high-temperature alloy. The gamma'phase reinforced cobalt-based high-temperature alloy for the LPBF process comprises the following elements: 27-32% of Ni; 11%-13% of Ta; 4 to 6 percent of Al; 4-5% of V; 1-2% of Ti; and the balance of Co. The preparation method comprises the steps that alloy element materials are smelted and prepared into cobalt-based alloy spherical powder, the obtained cobalt-based alloy spherical powder is placed in a laser powder bed fusion printing device, and the cobalt-based alloy spherical powder is prepared into a workpiece in a set shape; a unique net-shaped gamma'precipitated phase is formed, the traditional square block-shaped L12 morphology structure is broken, and the structure has excellent room-temperature and high-temperature mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal additive manufacturing, and in particular relates to a γ' phase strengthened cobalt-based high-temperature alloy for a laser powder bed fusion (LPBF) process and a preparation method thereof. Background Art

[0002] Superalloys are widely used in key hot-end components such as aerospace and gas turbines due to their excellent high-temperature strength, oxidation resistance and creep resistance. At present, superalloys with application value can be divided into nickel-based superalloys and cobalt-based superalloys according to the matrix elements, and can be divided into solid solution-strengthened superalloys and precipitation-strengthened superalloys according to the type of alloy strengthening. Typical γ' phase (L12 phase) precipitation-strengthened superalloys usually use traditional processes such as directional solidification to obtain columnar crystals and single crystal structures, and obtain a high volume fraction of γ' precipitation phase through aging heat treatment to ensure that the superalloy meets the working conditions. The γ' phase morphology of this traditional casting material is usually close-packed square blocks. If this organizational morphology can be broken, it may bring the possibility of improving mechanical properties. However, γ' phase precipitation-strengthened superalloys with a high volume fraction usually have strong non-weldability, and usually have a large number of crack defects in the additive manufacturing process, which is difficult to form, which poses a huge challenge to process optimization. The emergence of metal additive manufacturing technology has achieved a technological revolution compared to the high cost problem of traditional processes. Among the many metal additive manufacturing technologies, laser powder bed fusion (LPBF) technology is the most widely used and most deeply researched one, which uses a focused laser beam to selectively fuse metal powder particles layer by layer. This technology has an extremely high forming temperature, which can fully melt the metal powder during the manufacturing process, thereby producing high-density parts. LPBF has significant advantages such as high material utilization, stable manufacturing process, high processing accuracy and fewer post-processing steps. In the LPBF process, the temperature gradient of the molten pool is opposite to the material building direction, similar to the directional solidification process, and finally a strongly textured columnar crystal structure is obtained.

[0003] The heat treatment process of high-temperature alloys is often a two-step process of solution heat treatment and aging heat treatment. The former is to eliminate the segregation of elements inside the material, and the latter is to fully precipitate the γ' phase, so that the material has good high-temperature mechanical properties. During the LPBF process, the complex thermal history leads to the formation of high-density dislocations, especially in high-temperature alloy materials, where high-density dislocation cell structures usually appear. This high-density dislocation structure will cause the material to recrystallize during the solution heat treatment process, thereby losing its natural strong texture and columnar crystal structure, and the mechanical properties of the material are relatively poor.

[0004] It can be seen that in the existing technology, the traditional close-packed block-shaped L12 precipitation phase morphology structure constrains performance optimization. Many L12-strengthened high-temperature alloys usually show a large number of cracks and pore defects during the LPBF process, lacking an effective process control strategy. The high-temperature alloys prepared by LPBF technology have a high-density dislocation structure, which is easy to induce recrystallization during the solution-aging heat treatment process, causing the printed samples to lose the advantages of columnar crystals and strong textures. Summary of the invention

[0005] The object of the present invention is to overcome at least one of the above-mentioned deficiencies of the prior art, and to provide a γ' phase strengthened cobalt-based high temperature alloy for laser powder bed fusion (LPBF) process and a preparation method thereof, wherein the material has excellent mechanical properties.

[0006] The technical solution of the present invention is: a γ' phase strengthened cobalt-based high-temperature alloy for LPBF process, comprising the following elements (each element is composed of the following in mass percentage): Ni: 27-32%; Ta: 11%-13%; Al: 4-6%; V: 4-5%; Ti: 1-2%; the balance is Co.

[0007] Specifically, the following elements are included: Ni: 28.4% to 30.6%; Ta: 11.2% to 12.4%; Al: 4.2% to 5.8%; V: 4.1% to 4.6%; Ti: 1.2% to 1.8%; and the balance is Co.

[0008] Specifically, the composition of the alloy is calculated by mass percentage: Ni: 29.4%; Ta: 11.82%; Al: 4.51%; V: 4.21; Ti: 1.63%; and the balance is Co.

[0009] The present invention also provides a method for preparing a γ' phase strengthened cobalt-based high-temperature alloy, which is used to prepare the above-mentioned γ' phase strengthened cobalt-based high-temperature alloy, comprising the following steps:

[0010] Raw material configuration steps: weigh the alloying elements according to the following mass percentages: Ni: 27-32%; Ta: 11%-13%; Al: 4-6%; V: 4-5%; Ti: 1-2%; the balance is Co;

[0011] Powder preparation step: The alloy element material obtained in the raw material configuration step is melted and prepared into a cobalt-based alloy spherical powder.

[0012] Specifically, the powder preparation step includes the following steps:

[0013] The alloy element material obtained in the raw material preparation step is melted into a master alloy, the master alloy is then prepared into an alloy mixture, and the alloy mixture is prepared into a cobalt-based alloy spherical powder by a vacuum gas atomization method.

[0014] Specifically, after obtaining the cobalt-based alloy spherical powder, the cobalt-based alloy spherical powder with a particle size of 15 to 53 μm is screened to obtain the screened cobalt-based alloy spherical powder.

[0015] Specifically, the particle size distribution of the cobalt-based alloy spherical powder after screening is: D10=26.682 μm; D50=41.983 μm; D90=65.844 μm.

[0016] Specifically, after obtaining the cobalt-based alloy spherical powder, the preparation method further includes a laser powder bed melting molding step:

[0017] The obtained cobalt-based alloy spherical powder is placed in a laser powder bed fusion printing device to form a product of a set shape.

[0018] Specifically, in the laser powder bed fusion molding step, the parameters of the laser powder bed fusion printing device are: laser power 85~100W, scanning speed 700~900mm / s, scanning spacing 25~40μm, layer thickness 25-35μm, and the scanning strategy is 67° counterclockwise rotation between layers.

[0019] Specifically, after the part is obtained through the laser powder bed fusion molding step, the part is subjected to aging heat treatment at 1000 degrees Celsius for 48 hours.

[0020] The present invention provides a γ' phase strengthened cobalt-based high-temperature alloy for LPBF process and a preparation method thereof. Ta and Ti elements play a key role in regulating the γ' phase morphology based on a high-density dislocation structure. Ti, as one of the γ' phase forming elements, enhances the high-temperature mechanical properties of the alloy. Ta is segregated in the γ' phase and is one of the strong stabilizing elements of the γ' phase, significantly improving the melting temperature and stability of the γ' phase and enhancing the high-temperature mechanical properties. Both Ta and Ti have a large atomic radius and a low diffusion rate. Therefore, during the LPBF process molding process, the two are easily segregated in the high-energy dislocation cell wall structure, which plays a key role in controlling the γ' phase precipitation morphology through subsequent aging heat treatment, which is beneficial to improving the mechanical properties of the material, and provides a preparation and subsequent heat treatment process of a γ' phase precipitation strengthened cobalt-based high-temperature alloy by laser powder bed melting process, and utilizes the unique density dislocation cell structure advantage of the printed part to regulate the γ' phase precipitation mode, forming a unique network γ' precipitation phase, breaking the traditional block-shaped L12 morphology structure, and the structure has excellent room temperature and high temperature mechanical properties. The process conditions designed in the present invention can avoid solution heat treatment, and while obtaining a uniform high-density network γ' phase precipitation phase, it can maintain columnar crystals and strong texture morphology for a long time at a condition as high as 1000°C, indicating that the structure has great thermal stability and good application effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] FIG. 1( a ) is a metallographic image of a first material provided in an embodiment of the present invention;

[0023] FIG. 1( b ) is a metallographic image of a second material provided in an embodiment of the present invention;

[0024] FIG1( c ) is a metallographic image of a third material provided in an embodiment of the present invention;

[0025] FIG1( d ) is a metallographic image of a fourth material provided in an embodiment of the present invention;

[0026] FIG. 2( a ) is a diagram showing the grain orientation of a printed deposited material in the printed xy plane according to an embodiment of the present invention;

[0027] FIG2( b ) is a projection diagram of the polar figure of the (100) crystal plane of the printed deposited material in an embodiment of the present invention on the xy plane;

[0028] FIG2( c ) is a diagram showing the grain orientation of the printed deposited material on the printed yz plane in an embodiment of the present invention;

[0029] FIG2( d ) is a grain orientation diagram of the material in the heat-treated state in the printing xy plane according to an embodiment of the present invention;

[0030] FIG2(e) is a projection diagram of the (100) crystal plane pole figure of the heat-treated material in an embodiment of the present invention on the xy plane;

[0031] FIG. 2( f ) is a grain orientation diagram of the material in the heat-treated state on the printed yz plane in an embodiment of the present invention.

[0032] FIG3( a ) is a scanning electron microscope image of a typical scattered electron mode of a printed deposition state in an embodiment of the present invention;

[0033] FIG3( b ) is a scanning electron microscope image of a typical scattered electron mode of a printed deposition state in an embodiment of the present invention;

[0034] FIG3( c ) is a scanning electron microscope image of a typical scattered electron mode of a heat-treated state in an embodiment of the present invention;

[0035] FIG3( d ) is a scanning electron microscope image of a typical scattered electron mode of a heat-treated state in an embodiment of the present invention;

[0036] Figure 4Schematic diagram of the formation mechanism of the γ / γ' dual-phase structure in an embodiment of the present invention;

[0037] FIG5(a) is a graph showing an engineering stress-strain curve of a γ' phase strengthened cobalt-based high-temperature alloy in a heat-treated state under room temperature tensile stress according to an embodiment of the present invention;

[0038] FIG. 5( b ) is a graph showing the engineering stress-strain curve of the γ′ phase strengthened cobalt-based high temperature alloy under high temperature compression conditions at 800 degrees Celsius in an embodiment of the present invention. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0040] The various specific technical features and embodiments described in the specific implementation methods can be combined in any suitable manner unless there is any contradiction. For example, different implementation methods can be formed by combining different specific technical features / embodiments. In order to avoid unnecessary repetition, the various possible combinations of the specific technical features / embodiments in the present invention will not be described separately.

[0041] A γ' phase strengthened cobalt-based high-temperature alloy for LPBF process provided by an embodiment of the present invention comprises the following elements (by mass percentage), each element is composed by mass percentage as follows: Ni: 27-32%; Ta: 11%-13%; Al: 4-6%; V: 4-5%; Ti: 1-2%; the remainder is Co and unavoidable impurities, wherein Ta and Ti play a key role in regulating the γ' phase morphology based on high-density dislocation structure. Ti, as one of the γ' phase forming elements, enhances the high-temperature mechanical properties of the alloy. Ta is segregated in the γ' phase and is one of the strong stabilizing elements of the γ' phase, significantly improving the melting temperature and stability of the γ' phase and enhancing the high-temperature mechanical properties. Both Ta and Ti have large atomic radii and low diffusion rates, so in the LPBF process forming process, the two are easily segregated in the high-energy dislocation cell wall structure, which plays a key role in controlling the γ' phase precipitation morphology through subsequent aging heat treatment, and is conducive to improving the mechanical properties of the material.

[0042] Specifically, the γ' phase strengthened cobalt-based high temperature alloy comprises the following elements (by mass percentage): Ni: 28-31%; Ta: 11%-12.8%; Al: 4.1-5.9%; V: 4.05-4.85%; Ti: 1.1-1.9%; the balance is Co. In this embodiment, the γ' phase strengthened cobalt-based high temperature alloy comprises the following elements (by mass percentage): Ni: 28.4-30.6%; Ta: 11.2%-12.4%; Al: 4.2-5.8%; V: 4.1-4.6%; Ti: 1.2-1.8%; the balance is Co.

[0043] Specifically, the alloy components in the obtained product are calculated by mass percentage as follows: Ni: 29.4%; Ta: 11.82%; Al: 4.51%; V: 4.21; Ti: 1.63%; and the balance is Co.

[0044] The present invention also provides a method for preparing a γ' phase strengthened cobalt-based high temperature alloy, which is used to prepare the above-mentioned γ' phase strengthened cobalt-based high temperature alloy for laser powder bed melting process, comprising the following steps:

[0045] Raw material configuration steps: weigh the alloy element materials according to the following mass percentages: Ni: 27-32%; Ta: 11%-13%; Al: 4-6%; V: 4-5%; Ti: 1-2%; the balance is Co.

[0046] Powder preparation step: the alloy element materials obtained in the raw material configuration step are melted and prepared into cobalt-based alloy spherical powder. After the materials are mixed and melted, a molten alloy mixture is obtained. The molten alloy mixture can be prepared into cobalt-based alloy spherical powder by vacuum gas atomization or the like. The process is carried out under vacuum conditions. The molten alloy mixture is atomized into fine droplets by a high-pressure airflow. The droplets solidify into spherical particles in flight to obtain cobalt-based alloy spherical powder. The produced cobalt-based alloy spherical powder particles have regular shapes, are mostly spherical or nearly spherical, and have a smooth surface.

[0047] Specifically, the powder preparation step includes the following steps:

[0048] The alloy element material obtained in the raw material configuration step is melted into an intermediate alloy, and the intermediate alloy is then prepared into an alloy mixture, and the alloy mixture is prepared into a cobalt-based alloy spherical powder by a vacuum gas atomization method (under a protective gas atmosphere). Under the protection of the protective gas, the metal liquid formed by the melting of the alloy mixture flows out through a heat-insulating crucible and a guide nozzle, and the metal liquid is atomized and broken into a large number of fine droplets by a high-pressure airflow through a nozzle, and the droplets solidify into spherical cobalt-based alloy spherical powder particles in flight. In a specific application, the protective gas is an inert gas, such as argon, and its purity is not less than 99.999%.

[0049] Specifically, after obtaining the cobalt-based alloy spherical powder, the cobalt-based alloy spherical powder with a particle size of 15 to 53 μm is screened to obtain the screened cobalt-based alloy spherical powder.

[0050] Specifically, the particle size distribution of the cobalt-based alloy spherical powder after screening is: D10=26.682 μm; D50=41.983 μm; D90=65.844 μm.

[0051] Specifically, after obtaining the cobalt-based alloy spherical powder, the preparation method further includes a laser powder bed melting molding step:

[0052] The obtained cobalt-based alloy spherical powder is placed in a laser powder bed fusion printing device to form a product of a set shape.

[0053] Specifically, in the laser powder bed fusion molding step, the parameters of the laser powder bed fusion printing device are: laser power 85-100W, scanning speed 700-900mm / s, scanning spacing 25-40μm, layer thickness 25-35μm, and the scanning strategy is 67° counterclockwise rotation between layers. In specific applications, the laser power can be 90-100W, the scanning speed is 780-850mm / s, the scanning spacing is 28-32μm, and the layer thickness is 28-32μm. In this embodiment, the laser power is 95W, the scanning speed is 800mm / s, the scanning spacing is 30μm, and the layer thickness is 30μm.

[0054] Specifically, after the part is obtained by the laser powder bed fusion molding step, the part is directly subjected to aging heat treatment at a set temperature (950 to 100 degrees Celsius) in a furnace for a set time (36 to 60 hours.

[0055] In this embodiment, after the product is obtained by the laser powder bed fusion molding step, the product is directly placed in a muffle furnace and subjected to aging heat treatment at 1000 degrees Celsius for 48 hours.

[0056] In this embodiment, after obtaining the cobalt-based alloy spherical powder, a standard sieve is used to screen the product with a particle size of 15 to 53 μm to obtain a cobalt-based high-temperature alloy material for a laser powder bed melting process. In this embodiment, the ICP composition test results show that the composition of the alloy is calculated by mass percentage: Ni: 29.40%; Ta: 11.82%; Al: 4.51%; V: 4.21; Ti: 1.63%; the remainder is Co. The laser particle size test shows that the particle size distribution of the alloy is D10 = 26.682 μm; D50 = 41.983 μm; D90 = 65.844 μm.

[0057] The material was prepared using the Easy Plus 3D EP-M150 laser powder bed fusion printer. After experimental optimization, the process window was determined to be: laser power 95W, scanning speed 800mm / s, scanning spacing 30μm, layer thickness 30μm, and the scanning strategy was 67° counterclockwise rotation between layers. In order to optimize the airflow environment in the printing chamber, laser scanning angles of 70 to 290° were excluded. The printing environment was argon, and the oxygen content was controlled within 200ppm. The present invention uses a special low-power, low-scanning spacing, and high-scanning speed printing process to successfully achieve defect-free printing.

[0058] Figure 1(a) to Figure 1(d) The metallographic images of materials corresponding to different processes under similar volume energy density conditions are shown: Figure 1(a) corresponds to a power of 200W, a scanning speed of 800mm / s, and a scanning spacing of 60μm; Figure 1(b) corresponds to a power of 95W, a scanning speed of 800mm / s, and a scanning spacing of 30μm; Figure 1(c) corresponds to a power of 85W, a scanning speed of 400mm / s, and a scanning spacing of 50μm; Figure 1(d) corresponds to a power of 125W, a scanning speed of 400mm / s, and a scanning spacing of 80μm. It can be seen that while maintaining a similar volume energy density (around 135J / mm3), with a fixed layer thickness of 30μm, only low power, low scanning spacing, and high scanning speed can achieve relatively defect-free printing success, while other process parameters show a large number of crack defects and pore defects.

[0059] In this embodiment, the composition of the cobalt-based high-temperature alloy material is calculated by mass percentage: Ni: 29.40%; Ta: 11.82%; Al: 4.51%; V: 4.21; Ti: 1.63%; the balance is Co. Laser particle size test shows that the particle size distribution of the alloy is D10 = 26.682μm; D50 = 41.983μm; D90 = 65.844μm. Parameters of laser powder bed melting printing: laser power 95W, scanning speed 800mm / s, scanning spacing 30μm, layer thickness 30μm, and scanning strategy is 67° counterclockwise rotation between layers. After the cobalt-based high-temperature alloy material is obtained by the laser powder bed melting molding step, the part is directly placed in a muffle furnace and subjected to aging heat treatment at 1000 degrees Celsius for 48 hours.

[0060] Based on DSC testing, the γ' phase dissolution temperature was determined to be 1244.96 degrees Celsius, the solidus was 1314.12 degrees Celsius, and the liquidus was 1377.92 degrees Celsius. In order to avoid the recrystallization problem mentioned in the technical problems and defects and maintain the strong texture and columnar crystal morphology of the alloy, the present invention does not use the traditional two-step solid solution-aging heat treatment, but uses a muffle furnace for direct aging heat treatment at 1000 degrees Celsius for 48 hours, and can obtain two materials: the original printed deposition state and the direct aging heat treatment.

[0061] EBSD tests were performed on the printed deposited and heat treated (direct aging heat treated) materials, and the results are shown in Figures 2(a) to 2(f) It can be found that the cobalt-based high-temperature alloy involved in the present invention has excellent thermal stability, and maintains a strong <001> texture and columnar crystal morphology in both the printed deposition state and the heat-treated state.

[0062] Figure 2(a) to Figure 2(c) are the grain orientation diagrams of the printed deposited material in the printed xy plane, the projection of the (100) crystal plane pole figure on the xy plane, and the grain orientation diagram on the yz plane; Figure 2(d) to Figure 2(f) are the corresponding grain orientation diagrams of the heat-treated state.

[0063] Figure 3(a) to Figure 3(d) Figure 3 is a typical SEM image of the printed deposited state and the heat treated state in the scattered electron mode. Figure 3 is a typical SEM image, printed deposited state: (a) surface and (c) side. Heat treated state: (b) surface and (d) side. It can be found that the printed deposited state presents a high-density dislocation cell structure unique to the printing process, and the dislocation cell wall contrast is high, indicating that the dislocation cell is enriched with heavy metal elements (especially Ta), and this element segregation regulates the γ' precipitation behavior. The heat treated state photo forms a typical uniform γ / γ' dual-phase structure, the lower contrast is the γ phase, and the higher contrast is the γ' phase. Different from the high-temperature alloy microstructure prepared by traditional processes, the γ' phase involved in the present invention shows precipitation and growth from the dislocation cell wall, and the precipitated phase morphology is highly correlated with the dislocation cell morphology, and finally the residual γ phase is in the dislocation cell center, forming a special microstructure.

[0064] Figure 4 The specific microstructure formation mechanism obtained in the embodiment of the present invention is described, that is, a schematic diagram of the specific γ / γ' dual-phase structure formation mechanism of the present invention is embodied.

[0065] Figures 5(a) and 5(b) are engineering stress-strain curves of the heat-treated state of the γ' phase-strengthened cobalt-based superalloy under room temperature tensile and 800 degrees Celsius high temperature compression conditions in the embodiment of the present invention. The loading direction of the load is the y direction of the printing preparation. The results show that the room temperature tensile yield strength of the heat-treated state is 623.00MPa, and the tensile strength is 1329.83MPa; the compressive yield strength at 800 degrees Celsius is 819.12MPa, and the compressive strength is 1359.66MPa. Under both test conditions, the heat-treated samples show good plastic deformation ability, indicating that the cobalt-based superalloy with network γ' phase precipitation strengthening based on the additive manufacturing process of the present invention has good room temperature and high temperature mechanical properties.

[0066] It can be seen that in the embodiment of the present invention, a γ' phase strengthened cobalt-based high temperature alloy and its preparation method for the laser powder bed fusion (LPBF) process are provided, a preparation and subsequent heat treatment process of a γ' phase precipitation strengthened cobalt-based high temperature alloy is provided, a defect-free printing process window is successfully designed, and the γ' phase precipitation mode is regulated by taking advantage of the unique density dislocation cell structure of the printed part, forming a unique network γ' precipitation phase, breaking the traditional block-shaped L12 morphology structure, and the structure has excellent room temperature and high temperature mechanical properties. The process conditions designed by the present invention can avoid solution heat treatment, and while obtaining a uniform high-density network γ' phase precipitation phase, it can achieve long-term maintenance of columnar crystals and strong texture morphology at up to 1000°C, indicating that the structure is extremely thermally stable and has a good application effect.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A γ' phase strengthened cobalt-based high temperature alloy for LPBF process, characterized in that: Includes the following elements: Ni: 27-32%; Ta: 11% ~ 13%; Al: 4 ~ 6%; V:4~5%; Ti: 1-2%; the balance is Co.

2. The γ' phase strengthened cobalt-based high temperature alloy according to claim 1, characterized in that: Includes the following elements: Ni: 28.4-30.6%; Ta: 11.2%~12.4%; Al: 4.2~5.8%; V: 4.1~4.6%; Ti: 1.2~1.8%; the balance is Co.

3. The γ' phase strengthened cobalt-based high temperature alloy according to claim 1, characterized in that: The composition of the alloy is calculated by mass percentage: Ni: 29.4%; Ta: 11.82%; Al: 4.51%; V: 4.21; Ti: 1.63%; and the balance is Co.

4. A method for preparing a γ' phase strengthened cobalt-based high-temperature alloy, characterized in that: The method for preparing the γ' phase strengthened cobalt-based high temperature alloy according to any one of claims 1 to 3 comprises the following steps: Raw material configuration steps: weigh each element material according to the following mass percentage: Ni: 27-32%; Ta: 11%-13%; Al: 4-6%; V: 4-5%; Ti: 1-2%; the balance is Co; Powder preparation step: the alloy element material obtained in the raw material configuration step is melted and prepared into a cobalt-based alloy spherical powder.

5. The preparation method according to claim 4, characterized in that: The powder preparation step comprises the following steps: The alloy element material obtained in the raw material preparation step is melted into a master alloy, the master alloy is then prepared into an alloy mixture, and the alloy mixture is prepared into a cobalt-based alloy spherical powder by a vacuum gas atomization method.

6. The preparation method according to claim 5, characterized in that: After obtaining the cobalt-based alloy spherical powder, the cobalt-based alloy spherical powder with a particle size of 15 to 53 μm is screened to obtain the screened cobalt-based alloy spherical powder.

7. The preparation method according to claim 6, characterized in that: The particle size distribution of the cobalt-based alloy spherical powder after screening is: D10=26.682 μm; D50=41.983 μm; D90=65.844 μm.

8. The preparation method according to any one of claims 4 to 7, characterized in that After obtaining the cobalt-based alloy spherical powder, the preparation method further comprises a laser powder bed melting molding step: The obtained cobalt-based alloy spherical powder is placed in a laser powder bed fusion printing device to form a product of a set shape.

9. The preparation method according to claim 8, characterized in that: In the laser powder bed fusion molding step, the parameters of the laser powder bed fusion printing device are: laser power 85~100W, scanning speed 700~900mm / s, scanning spacing 25~40μm, layer thickness 25-35μm, and the scanning strategy is 67° counterclockwise rotation between layers.

10. The preparation method according to claim 9, characterized in that: After the part is obtained through the laser powder bed fusion molding step, the part is subjected to aging heat treatment at 1000 degrees Celsius for 48 hours.

Citation Information

Patent Citations

  • Stable gamma' phase intensified Co-Ni-V-Al-base high temperature alloy

    CN109207799A

  • Gamma'-phase enhanced Co-Ni-Al-Ta-based high-temperature alloy

    CN111041278A

  • Co-Ni-based high-temperature alloy with stable gamma / gamma 'double-FCC phase coherent structure and high-temperature oxidation resistance and preparation method of Co-Ni-based high-temperature alloy

    CN117512405A

  • High-chromium-content cobalt-nickel-based high-temperature alloy for additive manufacturing and preparation method thereof

    CN117802387A

  • Cobalt-based high-temperature alloy powder for 3D printing as well as preparation method and application of cobalt-based high-temperature alloy powder

    CN118773483A